2015
DOI: 10.1108/jrim-05-2014-0023
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing media types and content orientations in Facebook for global brands

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
3
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(160 citation statements)
references
References 32 publications
6
141
3
10
Order By: Relevance
“…For example, they could not be special beer brands or be exclusively regional; and (ii) the brands had to participate regularly in social networking, with a certain frequency of posts. The main objective in choosing eight different brands was to control the effect of the brand on the dependent variable, a similar procedure used by Kim et al (2015), which controlled product category. The number of posts (2583), covering the period between December 2012 -February 2013, is significantly greater in number than those analyzed in previous studies on Facebook (De Vries et al, 2012;Kim et al, 2015;Sabate et al, 2014;Swani et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, they could not be special beer brands or be exclusively regional; and (ii) the brands had to participate regularly in social networking, with a certain frequency of posts. The main objective in choosing eight different brands was to control the effect of the brand on the dependent variable, a similar procedure used by Kim et al (2015), which controlled product category. The number of posts (2583), covering the period between December 2012 -February 2013, is significantly greater in number than those analyzed in previous studies on Facebook (De Vries et al, 2012;Kim et al, 2015;Sabate et al, 2014;Swani et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The most striking characteristic of the studies which analyze sharing as the dependent variable is that they usually do not attach it to viral marketing. They usually refer to it as consumer engagement (Cvijikj & Michahelles, 2013) or response (Kim et al, 2015) because the association of sharing with two other actions in the social network: comment and liking.…”
Section: Brand Content Categorization In Virtual Social Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Rohm et al (2013) identified five primary motives that drive consumers to interact with brands through social media. They include "entertainment", "brand engagement", "access to customer services and content", "product information" and "promotions" as quoted by [10].…”
Section: Segmenting Global Customersmentioning
confidence: 99%